Effects of Air Intake Pressure to the Engine Performance, Fuel Economy and Exhaust Emissions on a Small Gasoline Engine - Nik Rosli, Abdullah; Nafis Syabil, Shahruddin; R., Mamat; Aman Mohd, Ihsan Mamat; Aminuddin, Zulkifli (Faculty Mechanical Engineering, UMP, 2014)
The study presents the engine performance, fuel economy and exhaust emissions at variations of air intake pressure. In carburetor system, the air intake pressure is influenced by the degree of opening throttle plate and venturi effect which draw the fuel to the combustion chamber. The experimental work is carried out at variations of engine speed and load using a single cylinder four stroke gasoline engine attached with a dynamometer. The measured exhaust emissions compositions are used to determine the mode of combustion. The results show that the standard air intake system resulted in rich combustion which then led to incomplete combustion which is caused by less availability of air for the combustion process. Eliminating the air filter reduces the air flow restriction in the air intake system resulted in better combustion and less unburned components due to higher air availability. Higher air intake pressure is better in increasing the efficiency of combustion within a limited time to improve fuel economy, power output and exhaust emissions. Better combustion also leads to the reduced unburned components such as carbon (C), hydrogen (H2), carbon monoxide (CO) and hydroxide (OH) that resulted in cleaner emissions.